(untitled) (Research, Society and Development, 2021)
The objective of the present work was to evaluate the growth of juveniles of jundia, Rhamdia quelen, raised in net tanks, fed with diets with different levels of protein and energy, for 324 days. 6,300 fish were used, with an average weight of 47.39 ± 14.06g, which were distributed in 18 net tanks of 5m³ (1.70m X 1.70m X 2.00m), with a density of 70 fish/m3 (350 fish/net-tanks). The experimental design was in a factorial scheme (3x2x3) being: three levels of crude protein (25, 30 and 35%), two levels of digestible energy (3250 and 3500 kcal) and three repetitions. Feeding was carried out twice a day (9 am and 5 pm) with 50% of the calculated ration (10% of the animals’ weight) being offered in each feeding. A positive influence of the protein levels of the diet was observed on the final weight of the juveniles of jundia up to the level of 30% of crude protein. Regarding apparent feed conversion, better results were observed when fed diets above 30% crude protein. The jundia, R. quelen, presents better productive performance with diets containing 30% CP, regardless of DE concentrations, however, the use of 3.250 kcal of ED/kg is recommended.